THE FUNCTION OF REAK ARTS FOR CHILDREN TODAY IN CIBOLERANG VILLAGE, CINUNUK VILLAGE, CILEUNYI, BANDUNG DISTRICT - Andiana, Dinda; Firtikasari, Melsya (Cinematology: Journal Anthology of Film and Television Studies, 2023)
West Java has folk art that has various functions and forms, such as Reak art in Ciborelang Village, Cinunuk Village, Cileunyi District, Bandung Regency. The Reak art has changed its function from ritual, entertainment, to games. Children and adult men in Ciborelang Village, Cinunuk Village, play Reak at certain events, especially for children, Reak art is used as a game. The problem of this research is: What is the function of Reak art being played by children today? This study uses a qualitative approach with descriptive analysis method. Data collection was carried out by means of observation, interviews, and documentation studies and literature studies. The results were analyzed to answer the problems raised in this study. This study concluded that the Reak art played by children functions as a game to fill their free time after coming home from school or on holidays. The number of players is between 10 or 15 children aged around 10-15 years. The form of the show is carried out by helaran or procession using musical instruments, such as: drum, badublag, brung, tilingtit, tong and vocals (cheers). The clothes use everyday clothes, such as: t-shirts (long or short sleeves) and pants (long or short). Reak players wear a large mask property called a barokan made of wood that resembles a crocodile's mouth and can be moved open and closed, the body is covered by a burlap sack. The dance moves are carried out spontaneously with the feet stepping alternately, the body slightly lowered and the arms opened wide similar to the movement of the pencak, the head turns left and right. The Reak show gives meaning to children to express, be creative, work together, respect each other, and learn to organize.